Extracellular vesicles: a potential new player in antibody-mediated rejection in lung allograft recipients - Bansal, Sandhya; Arjuna, Ashwini; Franz, Brian; Guerrero-Alba, Alexa; Canez, Jesse; Fleming, Timothy; Rahman, Mohammad; Hachem, Ramsey; Mohanakumar, T. (Frontiers in Transplantation, 2023)
Identification of recipients with pre-existing antibodies and cross-matching of recipient sera with donor lymphocytes have reduced the incidence of antibody-mediated rejection (AMR) after human lung transplantation. However, AMR is still common and requires not only immediate intervention but also has long-term consequences including an increased risk of chronic lung allograft dysfunction (CLAD). The mechanisms resulting in AMR remain largely unknown due to the variation in clinical and histopathological features among lung transplant recipients; however, several reports have demonstrated a strong association between the development of antibodies against mismatched donor human leucocyte antigens (donor-specific antibodies [DSAs]) and AMR. In addition, the development of antibodies against lung self-antigens (K alpha1 tubulin and collagen V) also plays a vital role in AMR pathogenesis, either alone or in combination with DSAs. In the current article, we will review the existing literature regarding the association of DSAs with AMR, along with clinical diagnostic features and current treatment options for AMR. We will also discuss the role of extracellular vesicles (EVs) in the immunerelated pathogenesis of AMR, which can lead to CLAD.